Divide et impera: boundaries shape the plant body and initiate new meristems. Issue 2 (22nd September 2015) - Wang, Quan; Hasson, Alice; Rossmann, Susanne; Theres, Klaus
Summary: Boundaries, established and maintained in different regions of the plant body, have diverse functions in development. One role is to separate different cell groups, for example the differentiating cells of a leaf primordium from the pluripotent cells of the apical meristem. Boundary zones are also established during compound leaf development, to separate young leaflets from each other, and in many other positions of the plant body. Recent studies have demonstrated that different boundary zones share similar properties. They are characterized by a low rate of cell divisions and specific patterns of gene expression. In addition, the levels of the plant hormones auxin and brassinosteroids are down‐regulated in boundary zones, resulting in a low differentiation level of boundary cells. This feature seems to be crucial for a second important role of boundary zones, the formation of new meristems. The primary shoot meristem, as well as secondary and ectopic shoot meristems, initiate from boundary cells that exhibit competence for meristem formation. Contents Summary 485 I. Introduction 485 II. Development of boundary zones 486 III. Boundaries shape the leaf 491 IV. Boundary zones are launching pads for meristem formation 491 V. Conclusions/future perspectives 495 Acknowledgements 495 References 495